Climate Change and TESOL: Language, Literacies, and the Creation of Eco‐Ethical Consciousness. Issue 1 (16th November 2015) - Goulah, Jason
Abstract : This article calls on the field of TESOL to respond to the planet's growing climatic and ecological crisis, conceptualizing climate change beyond just standards‐based language and content curriculum. Climate change is also cultural and religious, and thus warrants broader consideration in TESOL. Drawing on theories of value creation and creative coexistence, the author considers climate change socioculturally, epistemologically, and ontologically toward the development of a value‐creative eco‐ethical consciousness. The author concludes with a critical instrumental case study that used ethnographic and discourse analytic methods to examine the effects of a standards‐based climate change unit among adolescent religious refugee English language learners (ELLs) from the former Soviet Union (FSU). Findings suggest these ELLs' curricular engagement developed their language, literacies, and content knowledge relative to climate science. It also fostered transformed perspectives and value creation toward an eco‐ethical consciousness consonant with their cultural religious identity expression. Intersecting multiple subareas of TESOL, including FSU learners, digital literacies, religion and spirituality, and standards‐based approaches, the case study findings have potentially broader transferability implications beyond climate change and language learning and instruction.